Self-Efficacy, Collectivism and Social Loafing of University Workers in Southwest Nigeria: Implications for Staff-Students’ Social Interactions - Ajiboye, Ruth Oluwatoyin; Olubela, Afolabi (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
Social loafing, a group behaviour, has been identified as the bane of productivity in corporate organisations. This has been attributed partly to employeesâ€™ psychological factors (self-efficacy and collectivism) amongst others. This study adopted the descriptive design and three federal universities in the south-west were purposively selected. Five hundred and sixty-five non-academic staff in the three distance learning centres/institutes participated in the study. Collectivism (r = 0.40) and self-efficacy (r = 0.30) had positive correlations with social loafing. Self-efficacy (Î² = -.17, t = 3.07)  and  collectivism (Î² = .30, t = 5.53) made contribution to the reduction of social loafing among workers. Workers should extend pleasant personalities to academic staff of the universities, and to their students because of their maturity and the nature of the programme.     Keywords:  Self-Efficacy, Collectivism, Social Loafing